Comprehensive review on catalytic degradation of Cl-VOCs under the practical application conditions. Issue 3 (1st February 2022) - Lin, Fawei; Xiang, Li; Zhang, Zhiman; Li, Na; Yan, BeiBei; He, Chi; Hao, Zhengping; Chen, Guanyi
Abstract: Chlorinated volatile organic compounds (Cl-VOCs) are characterized by severe toxicity, high chemical stability, and low biodegradability. As such, they are regarded as hazardous gas pollutants. However, Cl substitution brings higher tendency in catalyst deactivation by Cl deposition, and different behaviors with the presence of water, other VOCs, NO x, SO2, and heavy metals. In this review, we provide a systematic summary on the progress and achievements in Cl-VOC catalytic degradation from a holistic perspective. Six types of Cl-VOCs, that is dichloromethane, dichloroethane, vinyl chloride, trichloroethylene, chlorobenzene, and dichlorobenzene are selected to represent chlorinated alkanes, alkenes, and aromatics. Variations in degradation efficiency, long-term stability, and the effects of water and other components are summarized to provide an insight into the intrinsic process involved in Cl-VOC catalytic degradation. This review also highlights strategies for alleviating Cl poisoning to provide guidances on the development of catalysts for Cl-VOC efficient elimination under practical application conditions. Graphical abstract: UF0001